Effectiveness of Neuro-Linguistic Programming (NLP) Techniques in Enhancing Second Language Listening Skills - Zukhruf Rehman,; Dr. Noshaba Younus,; Aqsa Batool, (Dialogue Social Science Review (DSSR), 2025)
This study explores the effectiveness of Neuro-Linguistic Programming (NLP) techniques in enhancing second language (L2) listening skills among secondary school students in Faisalabad, Pakistan. The research employed a pre-test and post-test design, focusing on three key NLP techniques: modeling, matching, and mirroring. The pre-test and post-test assessments measured students' enjoyment of listening to English, their confidence in listening comprehension, and their efforts to improve their listening skills. A total of 70 students participated in the study, and the results showed significant improvements in all areas following the NLP intervention. Specifically, students reported increased enjoyment of English listening content, higher confidence in their listening abilities, and greater effort to improve their listening skills. Statistical analysis confirmed the effectiveness of the NLP techniques, with paired t-tests revealing significant differences in the pre-test and post-test results. This study suggests that NLP techniques can be an effective tool for improving second language listening skills, providing valuable insights for language educators seeking to enhance student engagement and listening comprehension. Keywords: NLP techniques, second language listening, language acquisition, modeling, matching, mirroring, educational intervention